In Silico Study of Bajakah Compounds (Spatholobus suberectus) to Protease SARS-CoV-2 Inhibitor - Norhayati Norhayati; Andika Andika; Aris Purwanto (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Coronavirus Disease 2019 or COVID-19 is caused by a virus called Severe Acute Respiratory Syndrome Coronavirus 2. Until now, there is no specific treatment guide in dealing with COVID-19 in Indonesia. The curative pharmacological therapy for COVID-19 used is antiviral such as lopinavir, ritonavir, and oseltamivir, currently based on trial and error. This study carried out a Molecular Docking Analysis of 16 compounds owned by the Bajakah plant (Spatholobus suberectus). Oseltamivir was used as a control, and validation was carried out on a natural ligand, namely boceprevir against the main protease CoV or Mpro, 7C6S and the result was 1.47 Å using Toshiba hardware and AutoDock Tools, ChemSketch, Discovery Studio, Avogadro, UCSF Chimera software. Lipinski Rules of Five (RO5) analysis and ADMET analysis using SWISSADME and admetSAR. Licochalcone A compound had the best binding energy and inhibition constant values of -7.98 kcal/mol and 1.42 ?M. In contrast, the 6-Methoxyeriodictyol compound had fewer binding energy and inhibition constants, namely -5.24 kcal/mol and 143.04 ?M, respectively. In addition to the licochalcone A compound, the afrormosin compound, 3'4'7'-trihydroxyflavone, formononetin, cajanin, and dihydrokaempferol showed good binding energy values and inhibition constants compared to oseltamivir (control), so that these compounds have the potential to inhibit Mpro SARS-COV-2 or the virus that causes COVID-19. Analysis of Lipinski Rules of Five and ADMET is used to determine the properties of a molecule on the pharmacokinetics of drugs in the human body, and the results obtained to meet the requirements so that it is potentially effective for oral consumption.